A metal-radical hetero-tri-spin SCM with methyl–pyrazole–nitronyl nitroxide bridges. Issue 34 (11th August 2021) - Huang, Xiaohui; Wang, Kang; Han, Jing; Xie, Junfang; Li, Licun; Sutter, Jean-Pascal
Abstract : A novel 2p–3d–4f SCM has been successfully achieved using a pyrazole substituted nitronyl nitroxide which exhibits dual relaxation processes. Abstract : The preparation, crystal structures, and magnetic properties of a family of hetero-tri-spin 1-D coordination polymers with the formula [Ln(hfac)3 Cu(hfac)2 (4-NIT-MePyz)2 ] (Ln = Gd, 1, Tb, 2, Dy, 3 ; hfac = hexafluoroacetylacetonate; 4-NIT-MePyz = 2-4-(1-methyl)-pyrazolyl-4, 4, 5, 5-tetramethylimidazoline-1-oxyl-3-oxide) are reported. In these complexes, the 4-NIT-MePyz radical acts as a linker to bridge the Cu II and Ln III ions through its pyrazole and aminoxyl groups to form a chain structure. Magnetic properties typical of spin-chains are observed for Dy and Tb derivatives but single-chain magnet (SCM) behavior was evidenced only for the Tb compound which is characterized by an energy gap for demagnetization Δ τ / k B of 31 K.